Um soldado do ofício: análise da trajetória intelectual de Eurípedes Simões de Paula nos anos 1940-1960 - Silva, Patricia Helena Gomes Da [UNIFESP] (2019)
Considered on of the most respected names int he History’s area in Brazil, Eurípedes Simões de Paula (1910-1977) has played a significant role of consolidation movement in the History area under university foundations in Brazil. Between 1940 and 1960, the historian involved into multiple activities in order to build up the former Faculty of Philosophy, Science and Letters of University of Sao Paulo (Faculdade de Filosofia, Ciências e Letras, Universidade de São Paulo - FFCL-USP) and the History área: student of the first Faculty’s classes, Simões de Paula established himself into meandering through the Faculty : he achieved of the Chair of the History of Ancient and Medieval Civilization int he University of Sao Paulo since the mid 1940s, he became Director of the Faculty in the 1950, where he founded the Revista de História, in order to provide the foundations in his academic, intellectual and historiographical’s project. At the 1960s, he enlarged his bases in external scope to Faculty in order to model his name and involvement on the foundation and consolidation of the Association of University Professors of History (Associação dos Professores Universitários de História – APUH). In this sense, the present investigation purposes assume the professional carrer of Simões de Paula as the object’s study. The focus on the period among 1940s and 1960s, which intends to initiate some views about the terms os consolidation of the historical knowledge produced by the University at the relevant moment to promote trajectories and intellectuals projects deliberated by individuals linked to institutionalise movement of Historical Studies in Brazil based upon the pillars in higher education post-1930. Initiating at the research question, the study dwells on analysis of the main sources which embrace the records held by Center of Assistance to Historical Research (Centro de Apoio à Pesquisa Histórica – CAPH) and among them, the personal archive of Eurípedes Simões de Paula, the issues of the Revista de História between 1950s and 1960s and the Symposia of Universtiy Professors of History’s Annals carried out in the 1960s, in order to consider the inserts of the historian in the several initiatives strive for the institutionalisation of historical studies at the University in Brazil. Despite the operations have undertaken by Simões de Paula and others individuals whom seek to accomodate hi at the meanders of the Brazilian Historiography’s memory whereas the great figure, his interventioins were not immune from several tensions, struggles and strains inside the moment of the affirmation of academic university historiography in Brazil, simultaneously as Simões de Paula sought to legitimise, to be renowed internally and externally in the scope at the Brazilian University